On the Generalized Reflective Function of the Three-Degree Polynomial Differential System. (2nd May 2019) - Zhou, Jian; Zhao, Shiyin
Abstract : The structure of the generalized reflective function of three-degree polynomial differential systems is considered in this paper. The generated results are used for discussing the existence of periodic solutions of these systems.